2017
DOI: 10.1016/j.anireprosci.2017.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and cell proliferation in porcine placental vascularization

Abstract: The placenta is a highly vascularized organ, indispensable tothe transfer of nutrients to the growing fetuses. During gestation, there exists an expansion of the placental vascular network through active angiogenesis. The aim of this research was to study cell proliferation and apoptosis through high resolution light microscopy (HRLM) and transmission electron microscopy (TEM) ultrastructure, immunohistochemistry for Ki67and caspase-3, determination of placental vascular area,and TUNEL assay. Crossbred sows pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
(42 reference statements)
1
6
0
Order By: Relevance
“…However, as determined by TUNEL assay in this study, apoptotic cells were barely detectable in chorioallantoic tissues during pregnancy. It has been shown that CASP3 proteins levels in porcine placental tissue are higher on Day 30 than on Days 60, 80, and 90 of pregnancy, what coincides with the expression pattern of CASP3 mRNA in this study (42). In ovine placentas, CASP3 and CASP9 proteins increase toward term, and the levels of active CASP3 and CASP9 are increased in placentas with intrauterine growth restriction pregnancy compared with normal pregnancy (43).…”
Section: Discussionsupporting
confidence: 87%
“…However, as determined by TUNEL assay in this study, apoptotic cells were barely detectable in chorioallantoic tissues during pregnancy. It has been shown that CASP3 proteins levels in porcine placental tissue are higher on Day 30 than on Days 60, 80, and 90 of pregnancy, what coincides with the expression pattern of CASP3 mRNA in this study (42). In ovine placentas, CASP3 and CASP9 proteins increase toward term, and the levels of active CASP3 and CASP9 are increased in placentas with intrauterine growth restriction pregnancy compared with normal pregnancy (43).…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, a peak expression of fetal FN and αvβ3 integrin was found at 60 days. This period coincides with a placental tissue remodeling moment in pigs, with essential modifications in the expression of molecules related to vascular and placental establishment ( Cristofolini et al 2013 , Sanchis et al 2017 , Fiorimanti et al 2018 , Stenhouse et al 2019 b ).…”
Section: Discussionmentioning
confidence: 95%
“…An imbalance between cell proliferation and cell death would result in tumor formation and growth [41]. And, hypoxia is a common characteristic in tumor microenvironment and could induce the upregulation of HIF-1 α , which induces angiogenesis and also activates many other target genes mediating cell proliferation and apoptosis of cancer [4244]. Cleaved caspase 3 is considered as an apoptosis marker and Ki 67 is considered as a proliferative cell marker in tumor formation [41, 45, 46].…”
Section: Discussionmentioning
confidence: 99%